STUDI FATWA DEWAN SYARIAH NASIONAL (DSN) TERHADAP APLIKASI KONVERSI AKAD PADA NASABAH YANG TIDAK PROSPEKTIF DI BMT UGT SIDOGIRI CABANG WARU SIDOARJO - Rizka Kurnia Anggriani (Maliyah : Jurnal Hukum Bisnis Islam, 2016)
Application conversion contract on prospective customers who are not in BMT UGT Sidogiri Waru Sidoarjo branch of the conversion contract mura>bah}ah to musya>rakah. Application conversion contract executed in BMT UGT Sidogiri Branch Waru Sidoarjo not only given to customers who are still prospective, but also given to customers who are not prospective. Conversion contract given to prospective customers who are not in BMT UGT Sidogiri Branch Waru Sidoarjo not in accordance with the National Islamic Fatwa Council (DSN) 49 / DSN-MUI / II / 2005, the incompatibility of the conversion contract awarded to prospective customers who are not. Although the conversion application that does not contract the prospective customer is not in accordance with the Fatwa of DSN 49 / DSN-MUI / II / 2005 on the conversion contract, goodwill BMT UGT Sidogiri Branch Waru Sidoarjo should be appreciated (given a positive response). Because motivation BMT UGT Sidogiri Branch Waru Sidoarjo still provide an opportunity for prospective customers who are not helping that any element that ties akadnya be finished soon. Based on the results of research conducted by the author in BMT UGT Sidogiri Branch Waru Sidoarjo, so that the author can advise customers who have done the conversion contract was monitored, in order to avoid financing problems again. Later in the provision of financing to new customers, the BMT UGT Sidogiri Waru Sidoarjo Branch should also be careful to avoid financing problems that could lead to a loss in BMT.